Electrolyte based on amido multi-element deep eutectic solvent, preparation method and sodium metal battery
By combining amide-based multi-element deep eutectic solvents, the problems of flammability of traditional electrolytes and high viscosity of deep eutectic electrolytes are solved, thereby improving the stability and safety of sodium metal batteries and realizing a high-performance electrolyte system.
Patent Information
- Application Number
- CN202510985275.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-07-17
- Publication Date
- 2025-12-02
AI Technical Summary
Existing traditional commercial electrolytes are flammable, and deep eutectic electrolytes have high viscosity and poor compatibility with sodium metal interfaces, leading to stability and safety issues in sodium metal batteries.
An amide-based multi-component deep eutectic solvent is used to form dynamic hydrogen bond coordination through the combination of sodium salt, hydrogen bond donor, hydrogen bond acceptor and additives, thereby reducing the viscosity of the eutectic electrolyte and improving its interfacial compatibility with sodium metal, thus constructing a stable SEI layer.
An electrolyte with high safety, low viscosity, and a wide electrochemical window was achieved, improving the cycle stability and safety performance of sodium metal batteries.
Smart Images

Figure CN121054809A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of sodium metal battery technology, specifically to an electrolyte based on an amide-based multi-element deep eutectic solvent, its preparation method, and a sodium metal battery. Background Technology
[0002] Electrochemical energy storage boasts advantages such as high energy conversion efficiency, large-scale application, and rapid response, effectively solving the problems of energy storage and allocation. As a prominent representative of electrochemical energy storage technology, lithium-ion batteries have gained widespread attention due to their high energy density and long cycle life, and are widely used in electric vehicles and portable electronic devices. However, the scarcity and uneven distribution of lithium resources have led to a continuous increase in the cost of lithium-ion batteries, hindering their further development. Sodium-ion batteries share similar physicochemical properties and energy storage mechanisms with lithium-ion batteries, and sodium resources are abundant, plentiful in the Earth's crust, and inexpensive, making them considered the most promising battery system for large-scale energy storage and conversion in the post-lithium-ion era. Among the many sodium-ion battery anode materials currently available, sodium metal anodes stand out due to their high specific capacity (1166 mAh g / g). -1 It features low electrode potential (-2.714 vs. standard hydrogen electrode) and low bulk density (0.971 g / cm³). -3 Sodium metal, with its advantages such as high reactivity and low electrode potential, is considered one of the most promising anode materials for next-generation high-energy sodium-ion batteries. However, due to its high reactivity and low electrode potential, sodium metal exhibits poor stability in battery systems. This leads to a series of problems, including an unstable solid-state electrolyte interphase (SEI), uncontrolled sodium dendrite growth and the formation of "dead sodium," as well as unlimited volume expansion. These issues significantly reduce battery cycle life and safety performance, severely limiting the further application of sodium metal anodes. Notably, increasing research confirms that the unstable SEI is a key factor hindering the practical application of sodium metal batteries.
[0003] Constructing a stable SEI layer to protect the sodium metal anode and induce Na +Uniform deposition and suppression of sodium dendrite growth are key to improving the performance of sodium metal batteries. Researchers have made significant efforts in this regard, primarily including the design of novel sodium anode structures, the construction of artificial SEI layers, and electrolyte engineering optimization. While novel sodium host structures and artificial SEI layers can effectively suppress sodium dendrite growth to some extent, their fabrication processes are complex, and the high impedance interface between the artificial SEI layer and sodium metal further limits their practical application. In contrast, the electrolyte, as the main source and core element for SEI layer formation and evolution, plays a decisive role in battery operation. The composition and physicochemical properties of the electrolyte directly affect the ion solvation structure, electrochemical window, electrode material stability, the reversibility of sodium metal deposition / exfoliation, and deposition morphology. Therefore, electrolyte engineering optimization is the fundamental approach to constructing a stable electrode-electrolyte interface layer. Current research mainly focuses on the optimization and modification of traditional ether / ester electrolytes and the development of novel electrolyte systems. Traditional electrolyte optimization and modification mainly includes solvent-sodium salt optimization, concentration optimization, and the introduction of functional additives, but these methods often come at the cost of sacrificing some battery performance. Furthermore, traditional ether / ester electrolytes pose safety hazards such as volatility, flammability, and poor thermal stability. Therefore, developing novel electrolyte systems with high safety, a wide electrochemical window, and excellent electrochemical performance has become a current research hotspot and is of great significance for constructing high-energy-density sodium battery systems.
[0004] Deep eutectic electrolytes, as a representative of novel electrolyte systems, have broad potential applications in sodium metal batteries due to their advantages such as high thermal stability, non-flammability, wide electrochemical window, and designable composition. However, current deep eutectic electrolytes suffer from problems such as high viscosity, low ionic conductivity, and poor interfacial compatibility with sodium metal. Therefore, this invention provides an electrolyte based on an amide-based multi-component deep eutectic solvent, which can effectively solve the bottleneck problems of deep eutectic electrolytes in sodium metal battery applications, providing a new approach for designing and developing high-safety and high-performance sodium-based electrolytes. Summary of the Invention
[0005] The purpose of this invention is to provide an electrolyte based on an amide-based multi-element deep eutectic solvent, a preparation method thereof, and a sodium metal battery. This invention aims to solve the problems of flammability of existing traditional commercial electrolytes and the high viscosity and poor compatibility of deep eutectic electrolytes with sodium metal interfaces, so as to construct a high-performance electrolyte for sodium metal batteries.
[0006] To achieve the above objectives, the present invention adopts the following technical solution:
[0007] The first aspect of this invention is to provide an electrolyte based on an amide-based multi-element deep eutectic solvent, comprising: a sodium salt, a hydrogen bond donor, a hydrogen bond acceptor, and an additive, wherein the hydrogen bond donor is an amide solvent, the hydrogen bond acceptor is at least one selected from isocyanate compounds and sulfonyl compounds, and the additive is one of cyclic carbonate compounds; wherein the molar ratio of the sodium salt, hydrogen bond donor, and hydrogen bond acceptor is 1:1:1 to 1:10:10, and the mass of the additive is 0.1% to 10.0% of the total mass of the electrolyte. The amide solvent includes compounds with the following structural formula (A);
[0008]
[0009] In structural formula (A), R1 is one of methyl or trifluoromethyl, and R2 is preferably one of hydrogen, methyl, ethyl or methoxy.
[0010] Furthermore, the amide solvent is selected from at least one of the amide compounds shown in structural formulas (A-1), (A-2), (A-3), and (A-4);
[0011]
[0012] (A-1): Acetamide EA; (A-2): N-methylacetamide NMA; (A-3): Trifluoroacetamide TFA; (A-4): N-methyltrifluoroacetamide NMTFA.
[0013] Furthermore, the hydrogen bond acceptor is at least one of isocyanate compounds and sulfonyl compounds;
[0014] Furthermore, isocyanate compounds include one or more of hexamethylene diisocyanate (HDI) and 4-toluenesulfonyl isocyanate (PTSI);
[0015]
[0016] Furthermore, the sulfonyl compound RS(=O)2- includes one or more of vinyl sulfate DTD, sulfolane SL, 1,3-propanesulfonate lactone PES, and propenyl-1,3-sulfonate lactone PST.
[0017]
[0018] Furthermore, the sodium salt is selected from one or more of sodium bis(trifluoromethanesulfonyl)imide, sodium bis(fluorosulfonyl)imide, sodium hexafluorophosphate, sodium perchlorate, sodium tetrafluoroborate, or sodium difluorooxalate borate.
[0019] Furthermore, the additive is selected from a type of cyclic carbonate compound, preferably fluoroethylene carbonate.
[0020] In this invention, the deep eutectic solvent is a low-melting-point mixture formed by two or more components through weak intermolecular forces (mainly hydrogen bonds, van der Waals forces, and Lewis acid-base interactions), and its melting point is significantly lower than that of each individual component. Compared to traditional commercial electrolytes, deep eutectic solvents have advantages such as low vapor pressure, high thermal / chemical stability, wide electrochemical window, non-flammability, and adjustable composition, and are considered a promising new electrolyte system.
[0021] Amide-based deep eutectic electrolytes have attracted widespread attention due to their advantages such as high thermal stability, wide electrochemical window, high dielectric constant, and ionic conductivity. However, they suffer from poor interfacial compatibility with sodium metal, resulting in persistent interfacial side reactions, primarily attributed to the highly reactive interaction between sodium metal and the polar amide solvent. In structural formula (A), the carbonyl group C=O in the amide solvent exhibits a strong electron-withdrawing effect, enhancing the electronegativity of adjacent α-C / N atoms and thus increasing the activity of α-H and NH (which readily detach). The Lewis base sodium metal readily reacts with α-H and NH, producing hydrogen gas and other byproducts, leading to rapid performance degradation in sodium metal batteries. To address these issues, this invention, based on the strong Lewis acid-base interaction between sodium salt and amide solvent (strong Na-O coordination), introduces hydrogen bond acceptors (rich in N=C=O / O=S=S) to further form dynamic hydrogen bond coordination with the amide solvent (-NH), thereby preparing a multi-component deep eutectic electrolyte. Among these factors, the strong Lewis acid-base interaction endows the amide solvent with a strong coordination ability with Na metal ions, which helps to reduce Na+ ions. + - Anion coordination promotes sodium salt dissociation; secondly, the introduction of hydrogen bond acceptor compounds reduces the viscosity of the eutectic electrolyte while effectively weakening the activity of α-H and NH, significantly improving interfacial compatibility with sodium metal and constructing a stable SEI layer. The introduction of fluoroethylene carbonate as a film-forming additive helps form a dense SEI film and optimizes the Na+-hydrogenation process. + The diffusion, nucleation, and deposition behavior of these molecules further improves the safety performance and cycle life of the battery.
[0022] A second aspect of the present invention is to provide a method for preparing an electrolyte based on an amide-based multi-component deep eutectic solvent, comprising the following steps:
[0023] Step 1: Mix sodium salt, hydrogen bond donor, and hydrogen bond acceptor in a certain molar ratio and stir until a clear and transparent liquid is obtained;
[0024] Step 2: Add a certain amount of additive to the obtained clear and transparent liquid to obtain the multi-element deep eutectic electrolyte;
[0025] The molar ratio of sodium salt, hydrogen bond donor, and hydrogen bond acceptor is 1:1:1 to 1:10:10, and the mass of the additive is 0.1% to 10.0% of the total mass of the electrolyte.
[0026] The entire process was carried out in a glove box filled with argon gas, with water and oxygen content below 0.1 ppm.
[0027] A third aspect of the present invention is to provide a sodium metal battery comprising a positive electrode, a negative electrode, a separator, and an electrolyte, wherein the electrolyte of the aforementioned amide-based multi-element deep eutectic solvent is used as the electrolyte of the sodium metal battery.
[0028] Furthermore, the negative electrode is metallic sodium, and the positive electrode includes one or more of sodium vanadium phosphate, sodium iron pyrophosphate, sodium iron manganate, sodium iron phosphate, and sodium nickel manganate; the separator includes one of GF / A glass fiber separator, GF / F glass fiber separator, and GF / D glass fiber separator.
[0029] Compared with the prior art, the present invention has the following beneficial effects:
[0030] (1) Existing commercial ether / ester electrolytes have limitations in high voltage matching applications and safety hazards such as high flammability and low thermal stability. Amide-based multi-element deep eutectic electrolytes have high thermal / chemical stability, high safety, non-flammability, low cost, and simple preparation process. At the same time, the wide electrochemical window gives it the potential to be adapted to high voltage cathode materials.
[0031] (2) Based on the binary eutectic interaction of sodium salt and amide solvent, this invention further introduces hydrogen bond acceptors (rich in N=C=O / O=S=S) to form dynamic hydrogen bond coordination with the amide solvent (-NH), thereby preparing a multi-component deep eutectic electrolyte. The strong Lewis acid-base interaction endows Na metal ions with a strong coordination ability with the amide solvent, which helps to reduce Na... + - Anion coordination promotes sodium salt dissociation; secondly, the introduction of hydrogen bond acceptor compounds effectively weakens the activity of α-H and NH while reducing the viscosity of the eutectic electrolyte, thereby improving the interfacial compatibility and cycle stability with sodium metal.
[0032] (3) The amide-based multi-electrolyte deep eutectic electrolyte provided by this invention can effectively improve the electrode-electrolyte interface problem and optimize Na + The diffusion, nucleation, and deposition behavior of sodium dendrites is inhibited, thereby achieving long-term stable performance of sodium metal batteries. Attached Figure Description
[0033] Figure 1 Linear scan voltammetry of sodium metal / / stainless steel half-cells (Na / / SS) assembled with electrolytes prepared in Examples 1-8 and Comparative Examples 1-2;
[0034] Figure 2 AC impedance diagrams of stainless steel symmetrical cells (SS / / SS) assembled with electrolytes prepared in Examples 2, 6 and 8 and Comparative Example 2;
[0035] Figure 3 The following are differential scanning calorimetry (DSC) test results for the electrolytes in Example 2 and Comparative Example 2;
[0036] Figure 4 These are the electrolyte ignition test diagrams for Example 2 and Comparative Example 1;
[0037] Figure 5 Performance test graphs of sodium metal symmetric cells (Na / / Na) and Na / / Na3V2(PO4)3 full cells assembled with the electrolytes prepared in Example 2 and Comparative Examples 1-2.
[0038] Figure 6 The Raman spectra of the electrolytes in Example 2 and Comparative Example 2 are shown below. Detailed Implementation
[0039] The present invention provides an electrolyte based on an amide-based multi-element deep eutectic solvent, comprising: a sodium salt, a hydrogen bond donor, a hydrogen bond acceptor, and an additive. The hydrogen bond donor is an amide solvent, the hydrogen bond acceptor is at least one of an isocyanate compound and a sulfonyl compound, and the additive is one of a cyclic carbonate compound. The molar ratio of the sodium salt, hydrogen bond donor, and hydrogen bond acceptor is 1:1:1 to 1:10:10, and the mass of the additive is 0.1% to 10.0% of the total mass of the electrolyte. The amide solvent includes compounds with the following structural formula (A).
[0040]
[0041] In structural formula (A), R1 is one of methyl or trifluoromethyl, and R2 is preferably one of hydrogen, methyl, ethyl or methoxy.
[0042] In some embodiments of the present invention, the amide solvent is selected from at least one of the amide compounds shown in structural formulas (A-1), (A-2), (A-3), and (A-4);
[0043]
[0044] (A-1): Acetamide EA; (A-2): N-methylacetamide NMA; (A-3): Trifluoroacetamide TFA; (A-4): N-methyltrifluoroacetamide NMTFA.
[0045] In some embodiments of the present invention, the hydrogen bond acceptor is at least one of isocyanate compounds and sulfonyl compounds;
[0046] Isocyanate compounds include one or more of hexamethylene diisocyanate (HDI) and 4-toluenesulfonyl isocyanate (PTSI);
[0047]
[0048] Sulfonyl compounds RS(=O)2- include one or more of vinyl sulfate DTD, sulfolane SL, 1,3-propanesulfonate lactone PES, and propenyl-1,3-sulfonate lactone PST.
[0049]
[0050] In some embodiments of the present invention, the sodium salt is selected from one or more of sodium bis(trifluoromethanesulfonyl)imide, sodium bis(fluorosulfonyl)imide, sodium hexafluorophosphate, sodium perchlorate, sodium tetrafluoroborate, or sodium difluorooxalate borate. The additive is selected from cyclic carbonate compounds.
[0051] The present invention will be further described below with reference to specific embodiments. The embodiments of the present invention described below are generally only some, not all, of the embodiments based on the above technical solutions. Therefore, all other embodiments obtained by those skilled in the art based on the embodiments of the present invention without creative effort should fall within the scope of protection of the present invention.
[0052] Example 1
[0053] Sodium bis(trifluoromethanesulfonyl)imide (NaTFSI), N-methylacetamide (NMA), and hexamethylene diisocyanate (HDI) were mixed in an argon-filled glove box at a molar ratio of 1:4:1 and stirred until clear and transparent. Then, 5 wt% of fluoroethylene carbonate was added to prepare an amide-based multi-component deep eutectic electrolyte.
[0054] Example 2
[0055] Sodium bis(trifluoromethanesulfonyl)imide (NaTFSI), N-methylacetamide (NMA), and hexamethylene diisocyanate (HDI) were mixed in an argon-filled glove box at a molar ratio of 1:4:2 and stirred until clear and transparent. Then, 5 wt% of fluoroethylene carbonate was added to prepare an amide-based multi-component deep eutectic electrolyte.
[0056] Example 3
[0057] Sodium bis(trifluoromethanesulfonyl)imide (NaTFSI), N-methylacetamide (NMA), and hexamethylene diisocyanate (HDI) were mixed in an argon-filled glove box at a molar ratio of 1:4:3 and stirred until clear and transparent. Then, 5 wt% of fluoroethylene carbonate was added to prepare an amide-based multi-component deep eutectic electrolyte.
[0058] Example 4
[0059] Sodium bis(trifluoromethanesulfonyl)imide (NaTFSI), N-methylacetamide (NMA), and hexamethylene diisocyanate (HDI) were mixed in an argon-filled glove box at a molar ratio of 1:4:4 and stirred until clear and transparent. Then, 5 wt% of fluoroethylene carbonate was added to prepare an amide-based multi-component deep eutectic electrolyte.
[0060] Example 5
[0061] Sodium bis(trifluoromethanesulfonyl)imide (NaTFSI), N-methyltrifluoroacetamide (NMTFA) and hexamethylene diisocyanate (HDI) were mixed in an argon-filled glove box at a molar ratio of 1:4:2 and stirred until clear and transparent. Then, 5 wt% of fluoroethylene carbonate was added to prepare an amide-based multi-component deep eutectic electrolyte.
[0062] Example 6
[0063] Sodium bis(trifluoromethanesulfonyl)imide (NaTFSI), N-methylacetamide (NMA), and sulfolane (SL) were mixed in a 1:4:2 molar ratio in an argon-filled glove box and stirred until clear and transparent. Then, 5 wt% of fluoroethylene carbonate was added to prepare an amide-based multi-component deep eutectic electrolyte.
[0064] Example 7
[0065] Sodium bis(trifluoromethanesulfonyl)imide (NaTFSI), N-methylacetamide (NMA), and 1,3-propanesulfonic acid lactone (PES) were mixed in an argon-filled glove box at a molar ratio of 1:4:2 and stirred until clear and transparent. Then, 5 wt% of fluoroethylene carbonate was added to prepare an amide-based multi-component deep eutectic electrolyte.
[0066] Example 8
[0067] Sodium bis(trifluoromethanesulfonyl)imide (NaTFSI), N-methylacetamide (NMA), and propenyl-1,3-sulfonyl lactone (PST) were mixed in an argon-filled glove box at a molar ratio of 1:4:2 and stirred until clear and transparent. Then, 5 wt% of fluoroethylene carbonate was added to prepare an amide-based multi-component deep eutectic electrolyte.
[0068] Comparative Example 1
[0069] In an argon-filled glove box, 1M sodium hexafluorophosphate (NaPF6) was dissolved in ethylene carbonate (EC) and diethyl carbonate (DEC) in a volume ratio of 1:1 (v:v) to prepare an ester-based electrolyte of 1M NaPF6-EC:DEC (1:1).
[0070] Comparative Example 2
[0071] Sodium bis(trifluoromethanesulfonyl)imide (NaTFSI) and N-methylacetamide (NMA) were mixed in a 1:4 molar ratio in an argon-filled glove box and stirred until clear and transparent. Then, 5 wt% of fluoroethylene carbonate was added to prepare an amide-based binary deep eutectic electrolyte.
[0072] The mixed solvents prepared in Examples 1-8 and Comparative Examples 1-2 were used as the electrolytes for sodium metal batteries. Metallic sodium was used as the counter electrode, a stainless steel sheet as the working electrode, and a GF / D glass fiber membrane as the separator. A "sodium metal / electrolyte-wetted membrane / stainless steel sheet" half-cell (Na / / SS) was assembled. Electrochemical window testing was performed using linear sweep voltammetry (LSV) with a voltage range of 0.0–6.0 V and a scan rate of 0.1 mV / s. -1 .like Figure 1 As shown, the electrochemical stability windows of the multi-element deep eutectic electrolytes prepared in Examples 1-8 are all greater than 4.3V, indicating that they have high oxidation decomposition potentials and show high voltage cathode matching potential.
[0073] The mixed solvents prepared in Examples 2, 6, 8 and Comparative Example 2 were used as the electrolytes for sodium metal batteries. GF / D glass fiber membranes were used as separators to assemble symmetrical batteries (SS / / SS) consisting of a stainless steel sheet / a separator fully wetted with electrolyte and a stainless steel sheet. The ionic conductivity was tested using the impedance method, as shown in the following formula:
[0074] σ = L / AR
[0075] Where L is the distance between the two electrodes (cm);
[0076] A – Electrode area (cm²) 2 );
[0077] R – Internal resistance of the electrolyte (Ω).
[0078] The distance between the two electrodes was calibrated using vernier calipers. The electrode diameter was 16 mm. The internal resistance of the electrolyte was tested using the AC impedance method of an electrochemical workstation.
[0079] Depend on Figure 2 It can be seen that, according to calculations, the ionic conductivity of Examples 2, 6, and 8 is 3.31 mS / cm, respectively. -1 3.95mS cm -1 3.31mS cm -1 The value was higher than that of Comparative Example 2 (2.06 mS cm). -1 This demonstrates high ionic conductivity; further, it shows that the introduction of hydrogen bond acceptors can form strong hydrogen bond eutectic interactions with amide-based hydrogen bond donors, thereby reducing electrolyte viscosity and increasing ionic conductivity.
[0080] Figure 3 The image shows a comparison of differential scanning calorimetry (DSC) results for Example 2 and Comparative Example 2. The DSC analysis was conducted in a temperature range from room temperature to -120°C in liquid nitrogen at a cooling rate of 5°C / min. It can be seen that the solidification points T of the electrolytes in Example 2 and Comparative Example 2 are... m Disappearance, only the glass transition temperature T g This indicates that there is a deep eutectic effect between the electrolyte system, forming a deep eutectic electrolyte; and the freezing point of Example 2 is relatively low (-71.2℃), proving that on the basis of the Na-O Lewis acid-base interaction, the introduction of hydrogen bond acceptors can form a multi-element deep eutectic effect, further reducing the melting point.
[0081] Figure 4 The electrolyte ignition tests for Example 2 and Comparative Example 1 showed that Comparative Example 1 was ignited instantly and extinguished only after the components had completely burned, consistent with the inherent flammability of traditional carbonate electrolytes. In contrast, Example 2 showed no combustion after 5 seconds of ignition, and still did not burn after a second 5-second ignition, demonstrating the non-flammability and high safety of the obtained amide-based multi-component deep eutectic electrolyte.
[0082] Using the mixed solvent prepared in Example 2 and Comparative Examples 1-2 as the electrolyte for the sodium metal battery, and using metallic sodium as both the counter and working electrode, and a GF / D glass fiber membrane as the separator, a sodium metal symmetric battery (Na / / Na) was assembled. The battery was tested at 0.5 mA cm⁻¹. -2 0.5mAh cm -2 Under the conditions, it was found through testing that ( Figure 5 a) The sodium metal symmetric cell assembled in Example 2 exhibited stable deposition / stripping for over 410 hours, superior to Comparative Example 1 (220 hours) and Comparative Example 2 (280 hours); furthermore, as Figure 5 As shown in b, using metallic sodium as the counter electrode of a sodium metal battery, commercial sodium vanadium phosphate (Na3V2(PO4)3, NVP) as the working electrode, and a GF / D glass fiber membrane as the separator, a Na / / Na3V2(PO4)3 full cell was assembled and its electrochemical performance was tested. Within the operating voltage range of 2.5-4.0V, under 1C rate conditions, the initial discharge specific capacity of the full cell assembled in Example 2 was 101.2 mAh g. -1 The coulombic efficiency is 94.6%, and the reversible specific capacity is 86.9 mAh g after 250 cycles. -1 The capacity retention rate was 85.8%, far superior to comparative examples 1-2 (which experienced severe performance degradation below 100 cycles). This demonstrates that the introduction of hexamethylene diisocyanate (HDI), a hydrogen bond donor, enables strong hydrogen bonding coordination with amide solvents, effectively weakening the activity of α-H and NH, and improving interfacial compatibility with Na metal and long-term cycling stability.
[0083] Figure 6The images show the Raman spectra of the electrolytes in Example 2 and Comparative Example 2, used to investigate the formation mechanism of the amide-based multi-component deep eutectic electrolyte and the inhibitory effects of α-H and NH activities. The Raman spectra show that the characteristic peak of C=O (from NMA) starts from 1646 cm⁻¹. -1 Offset to 1657cm -1 The characteristic peak of O=C=N (from HDI) also shows a high wavenumber shift (2263 to 2275 cm⁻¹). -1 Furthermore, the peak intensity decreased; additionally, the characteristic peak of -NH (from NMA) disappeared in Example 2 (while it was present in Comparative Example 2). This is mainly attributed to Na + The strong Lewis acid-base eutectic effect of the C=O bond (from NMA) and the strong hydrogen bonding coordination between the O=C=N bond and the -NH bond in hexamethylene diisocyanate (HDI) can effectively weaken the single bond binding effect in each component. While promoting the dissociation of sodium salt and reducing viscosity, it can effectively inhibit the activity of α-H and NH, improve the compatibility of the electrolyte with the sodium metal interface, and thus form a multi-element deep eutectic electrolyte with a lower melting point.
[0084] In summary, this invention provides an electrolyte based on an amide-based multi-component deep eutectic solvent, its preparation method, and a sodium metal battery. Building upon the binary eutectic interaction between sodium salt and amide solvent, a hydrogen bond acceptor (rich in N=C=O / O=S=S) is further introduced to form dynamic hydrogen bond coordination with the amide solvent (-NH), thereby preparing a multi-component deep eutectic electrolyte. Specifically, the strong Lewis acid-base interaction endows the amide solvent with a strong coordination ability with Na metal ions, which helps to reduce Na... + - Anion coordination promotes sodium salt dissociation; secondly, the introduction of hydrogen bond acceptor compounds effectively weakens the activity of α-H and NH while reducing the viscosity of the eutectic electrolyte, thus improving the interfacial compatibility and cycle stability between the electrolyte and sodium metal. Furthermore, this electrolyte possesses advantages such as non-flammability, high thermal / chemical stability, a wide electrochemical window, and high ionic conductivity. Moreover, its preparation method is simple and can meet the needs of large-scale production. Therefore, this deep eutectic electrolyte has promising application prospects.
[0085] It should be understood that the application of the present invention is not limited to the examples above. Those skilled in the art can make improvements or modifications based on the above description, and all such improvements and modifications should fall within the protection scope of the appended claims.
Claims
1. An electrolyte based on an amide-based multi-component deep eutectic solvent, characterized in that, include: The electrolyte comprises a sodium salt, a hydrogen bond donor, a hydrogen bond acceptor, and an additive. The hydrogen bond donor is an amide solvent, the hydrogen bond acceptor is at least one of an isocyanate compound and a sulfonyl compound, and the additive is one of a cyclic carbonate compound. The molar ratio of the sodium salt, hydrogen bond donor, and hydrogen bond acceptor is 1:1:1 to 1:10:10, and the mass of the additive is 0.1% to 10.0% of the total mass of the electrolyte.
2. The electrolyte based on an amide-based multi-component deep eutectic solvent according to claim 1, characterized in that, The amide solvents include compounds with the following structural formula (A); In structural formula (A), R1 is one of methyl or trifluoromethyl, and R2 is one of hydrogen, methyl, ethyl or methoxy.
3. The electrolyte based on an amide-based multi-component deep eutectic solvent according to claim 2, characterized in that, The amide solvents are selected from at least one of the amide compounds shown in structural formulas (A-1), (A-2), (A-3), and (A-4); (A-1): Acetamide EA; (A-2): N-methylacetamide NMA; (A-3): Trifluoroacetamide TFA; (A-4): N-methyltrifluoroacetamide NMTFA.
4. The electrolyte based on an amide-based multi-component deep eutectic solvent according to claim 1, characterized in that, The hydrogen bond acceptor is at least one of isocyanate compounds and sulfonyl compounds; Isocyanate compounds include one or more of hexamethylene diisocyanate (HDI) and 4-toluenesulfonyl isocyanate (PTSI); Sulfonyl compounds RS(=O)2- include one or more of vinyl sulfate DTD, sulfolane SL, 1,3-propanesulfonate lactone PES, and propenyl-1,3-sulfonate lactone PST.
5. The electrolyte based on an amide-based multi-component deep eutectic solvent according to claim 1, characterized in that, The sodium salt is selected from one or more of sodium bis(trifluoromethanesulfonyl)imide, sodium bis(fluorosulfonyl)imide, sodium hexafluorophosphate, sodium perchlorate, sodium tetrafluoroborate, or sodium difluorooxalate borate.
6. The electrolyte based on an amide-based multi-component deep eutectic solvent according to claim 1, characterized in that, The additive is selected from one of the cyclic carbonate compounds, including but not limited to fluoroethylene carbonate.
7. A method for preparing an electrolyte based on an amide-based multi-component deep eutectic solvent as described in any one of claims 1-6, characterized in that, Includes the following steps: Step 1: Mix sodium salt, hydrogen bond donor, and hydrogen bond acceptor in a certain molar ratio and stir until a clear and transparent liquid is obtained; Step 2: Add a certain amount of additive to the obtained clear and transparent liquid to obtain the multi-element deep eutectic electrolyte; The molar ratio of sodium salt, hydrogen bond donor, and hydrogen bond acceptor is 1:1:1 to 1:10:10, and the mass of the additive is 0.1% to 10.0% of the total mass of the electrolyte. The entire process was carried out in a glove box filled with argon gas, with water and oxygen content below 0.1 ppm.
8. A sodium metal battery, characterized in that, It includes a positive electrode, a negative electrode, a separator, and an electrolyte, wherein the electrolyte is the electrolyte based on an amide-based multi-element deep eutectic solvent as described in any one of claims 1-7.
9. A sodium metal battery according to claim 8, characterized in that, The negative electrode is metallic sodium, and the positive electrode includes one or more of sodium vanadium phosphate, sodium iron pyrophosphate, sodium iron manganate, sodium iron phosphate, and sodium nickel manganate; the separator includes one of GF / A glass fiber separator, GF / F glass fiber separator, and GF / D glass fiber separator.